Experimental study on seepage characteristics model of tunnel lining based on infrared imaging - Zhijian Wu; Hua Wu; Yichen Peng; Renjie Song; Yimin Wu; Haiping Wu; Guangzheng Zhuang (Scientific Reports)
Abstract Lining seepage is one of the most prevalent structural diseases in tunnel engineering. The variability of lining crack types and the complexity of groundwater seepage conditions pose significant threats to tunnel safety and operational integrity. Most previous studies have focused primarily on the geometric characteristics of seepage areas, while the relationships between these geometric features and other influencing factors, as well as the development of quantitative indicators within infrared signatures for rapid crack pattern identification, have not been systematically explored. To investigate the influence of secondary lining crack patterns and seepage rate on infrared characteristics of seepage, this research innovatively creates a custom-designed seepage simulation device for tunnel secondary linings, and systematic studies on infrared features of seepage were conducted. The results show that: (1) Geometric characteristics of seepage areas for various crack types were systematically summarized, where crack patterns and their positions determine the geometric features of seepage regions; (2) Seepage areas of all crack types increase with flow rate, and different crack morphologies exhibit distinct susceptibility to flow rate at varied positions; (3) The centroid distance curve of the seepage core area derived from isothermal maps enables rapid identification of crack morphologies and their positions within the tunnel by analyzing curve patterns. This research lays a foundational basis for the rapid identification of water seepage areas in infrared detection technology for tunnel water leakage, while also providing theoretical support for promoting the transition from qualitative to quantitative analysis of water seepage areas in current infrared detection practices.